ETIKA KERJA DAN KUALITAS LAYANAN ISLAM TERHADAP KINERJA PERBANKAN PADA PT BANK SYARIAH MANDIRI PROVINSI LAMPUNG - Anna Thesya Saimona (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2018)
Performance is the pulse of a company that must get attenton in order to maintain the existence of the company in competing with other companies. This study aims to, (1) the effect of work ethics on banking performance, (2) the effect of the quality of Islamic services on banking performance, and (3) the effect off work ethics and quality o Islamic services at PT. Bank Syariah Mandiri Lampung Province. The approach used is desciptive quantitative. The sampling technique uses purposive sampling. The number of samples is 38 employeees at 4 Bank Syariah Mandiri that is PT Bank Syariah Mandiri Kedaton Kota Bandar Lampung, PT Bank Syariah Mandiri Kalirejo, PT Bank Syariah Mandiri Pringsewu dan PT Bank Syariah Mandiri Kota Metro. The results of the study is (1) the results of the T-test value on work ethics on banking performance has a sig value of 0.017 < 0.05, then work ethics influences the performance at PT Bank Syariah Mandiri Lampung Province, (2) the results off the T-test value the quality of Islamic services on banking performance have a sig value of 0.028 < 0.05 meaning that the quality of Islamic services affects the performance at PT Bank Syariah Mandiri Lampung Province, (3) The results of the F-test sig is 0.000 < 0.05 so that based on the sig value of work ethics and service quality simultaneously inffluence the PT Bank Syariah Mandiri Lampung Province.